2018
DOI: 10.3892/ijmm.2018.3886
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin protects the myocardium with hypoxia/reoxygenation treatment through upregulating the expression of growth hormone, growth hormone secretagogue receptor and insulin-like growth factor-1, and promoting the phosphorylation of protein kinase�B

Abstract: Ghrelin is an endogenous ligand of growth hormone (GH) secretagogue receptor (GHSR) and has a number of biological effects, including heart protection. The present study aimed to reveal the positive effect of ghrelin on myocardium with hypoxia/reoxygenation (H/R) treatment and the involved molecular mechanisms. Successful construction of lentiviral expression vector (ghrelin-pLVX-Puro) was confirmed by colony polymerase chain reaction (PCR) verification. Primary rat cardiac myocytes were isolated and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…In agreement with previously published data, the results of RPPA analysis (Fig. 4) showed that activation of GHSR‐1a strongly affects the pattern of cellular protein phosphorylation (69, 70). This suggests that ghrelin‐induced signaling cascades may affect transcription and translation factors such as NF‐κB, ERK, mTOR, and eEF2.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previously published data, the results of RPPA analysis (Fig. 4) showed that activation of GHSR‐1a strongly affects the pattern of cellular protein phosphorylation (69, 70). This suggests that ghrelin‐induced signaling cascades may affect transcription and translation factors such as NF‐κB, ERK, mTOR, and eEF2.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, other studies demonstrate that even four weeks after MI, intracellular calcium transients and contractile function could be improved via long-term treatment with Gh, which might at least partially be attributed to the increased protein levels of SERCA-2 upon treatment observed in this study [ 280 ]. An upregulation of Gh and Igf1 and subsequently increased phosphorylated AKT levels are also suggested to underlie the cardioprotective effect of ghrelin treatment [ 109 ] in cardiomyocytes undergoing hypoxia and reoxygenation [ 178 ]. Surprisingly, the growth hormone-releasing hormone (GHRH) agonist JI-38 is reported to promote cardiac repair after MI, independently of Gh or Igf1 [ 141 ], suggesting a direct signaling pathway of GHRH.…”
Section: Hormone-based Strategies For Cardiac Regenerationmentioning
confidence: 99%
“…9) Thus, we aimed to explore the functions of circ-USP39 in the progression of AMI. Since the occurrence of AMI is mainly related to hypoxia induced by ischemia, 10,11) we further explored the concrete mechanism of circ-USP39 in hypoxia-induced cardiomyocyte injury.…”
mentioning
confidence: 99%